Financial Challenges for School Principals During the Covid-19 Pandemic - Alina Cristina CĂLDĂRARU; Gabriella SZEKERES; Mihai PĂUNICĂ (Communications of International Proceedings, 2021)
The impact of Covid-19 pandemic was felt around all industries and sectors of the economy. Some studies identify the education as part of the directly hit sectors by the pandemic. While online learning and other forms of virtual learning innovations were introduced, the absence of students from campuses had significant financial impact on schools. This study was undertaken in the form of quantitative secondary research to determine from an accounting perspective the specific extent of financial challenge that the pandemic posed on principals. Findings from the study has proved that the overall quantum of funding that the schools received reduced significantly. This was particularly the case for pre-university institutions that rely more on external funding from government. The inadequate funding forced most principals to cut down on their budgets. In some schools, there was shortage of logistics to effectively undertake the virtual learning program. Going into the future, recommendations have been made on the need to diversify the sources of funding of pre-university institutions.
Keywords: COVID-19; Impact; Education; Challenges; Pre-university